Interest in the criminalzation of smoking - كويز اياد داوود (Journal of Legal Sciences, 2019)
Smoking is one of the biggest pests in societies and is one of the main threats to human health as the problem goes beyond the smoker and the non smoker around it and is transmitted through the air and produces what is known as passive smoking. Scientific studies and medical research confirm that at least 90% of patients with oral, pharyngeal, laryngeal, and other cancers are among smokers. It is known that the risk of these cancers among smokers increases as the amount of smoking increases. That the incidence of these malignant tumors among smokers rises between 6 to 10 times the incidence in non-smokers, Recent scientific research has proved beyond doubt that tobacco contains precursors, active carcinogens, activated cancer cells in cancer cells lining the gastrointestinal tract, as well as substances that facilitate the absorption of cancer-causing chemicals contained in smoke. The insistence on intensive smoking for many years caused by changes in the exposed cells leads to abnormal and aggressive growth that ends in cancerous transformation. Because of the economic damage caused by smoking to governments or individuals smokers and their families, for economic damage to governments is reflected that when governments are responsible for health care insurance, the diseases associated with smoking will make governments pay additional expenses for the treatment of these diseases, and countries (73%) of the world’s tobacco. This requires the use of large tracts of land to grow tobacco at the expense of areas devoted to food crops. Governments will also pay additional expenses for the maintenance and cleaning of public areas